A population‐based cost‐effectiveness study of early genetic testing in severe epilepsies of infancy. (11th May 2018) - Howell, Katherine B.; Eggers, Stefanie; Dalziel, Kim; Riseley, Jessica; Mandelstam, Simone; Myers, Candace T.; McMahon, Jacinta M.; Schneider, Amy; Carvill, Gemma L.; Mefford, Heather C.; ,; Scheffer, Ingrid E.; et al.
Summary: Objective: The severe epilepsies of infancy (SEI) are a devastating group of disorders that pose a major care and economic burden on society; early diagnosis is critical for optimal management. This study sought to determine the incidence and etiologies of SEI, and model the yield and cost‐effectiveness of early genetic testing. Methods: A population‐based study was undertaken of the incidence, etiologies, and cost‐effectiveness of a whole exome sequencing–based gene panel (targeted WES) in infants with SEI born during 2011‐2013, identified through electroencephalography (EEG) and neonatal databases. SEI was defined as seizure onset before age 18 months, frequent seizures, epileptiform EEG, and failure of ≥2 antiepileptic drugs. Medical records, investigations, MRIs, and EEGs were analyzed, and genetic testing was performed if no etiology was identified. Economic modeling was performed to determine yield and cost‐effectiveness of investigation of infants with unknown etiology at epilepsy onset, incorporating targeted WES at different stages of the diagnostic pathway. Results: Of 114 infants with SEI (incidence = 54/100 000 live births/y), the etiology was determined in 76 (67%): acquired brain injuries (n = 14), focal cortical dysplasias (n = 14), other brain malformations (n = 17), channelopathies (n = 11), chromosomal (n = 9), metabolic (n = 6), and other genetic (n = 5) disorders. Modeling showed that incorporating targeted WES increased diagnostic yield compared to investigation without targeted WES (48/86 vs 39/86). Early targeted WES had lower total cost (677 081 U.S. dollars [USD] vs 738 136 USD) than late targeted WES. A pathway with early targeted WES and limited metabolic testing yielded 7 additional diagnoses compared to investigation without targeted WES (46/86 vs 39/86), with lower total cost (455 597 USD vs 661 103 USD), lower cost per diagnosis (9904 USD vs 16 951 USD), and a dominant cost‐effectiveness ratio. Significance: Severe epilepsies occur in 1 in 2000 infants, with the etiology identified in two‐thirds, most commonly malformative. Early use of targeted WES yields more diagnoses at lower cost. Early genetic diagnosis will enable timely administration of precision medicines, once developed, with the potential to improve long‐term outcome.